OPTIMIZING THE ROLE OF THE SHARIA SUPERVISORY COUNCIL (DPS) AT THE ZISWAF INSTITUTION - Mohammad Adnan; Badrah Uyuni (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
This study aims to discuss the role played by the Sharia Supervisory Board in Amil Zakat Institutions in Indonesia. This type of research uses a qualitative descriptive method using literature study data as the primary data and observations as supporting data. The results of this study show that the Sharia Supervisory Board plays a role in implementing sharia compliance of zakat institutions as supervisors and advisers. The role of DPS empirically, apart from providing sharia opinions, sharia fatwas. It has become the role of DPS to provide zakat-related education to actors in zakat institutions. DPS has a vital and positive role in the quality of financial reporting because, on the other hand, muzakki requires transparency and accountability for using zakat funds. The Sharia Supervisory Board (DPS) must ensure that zakat funds are calculated correctly, reported transparently, and distributed evenly to zakat recipients. Penelitian ini bertujuan untuk membahas peran Dewan Pengawas Syariah dalam Lembaga Amil Zakat di Indonesia. Jenis penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan data studi literatur sebagai data primer dan observasi sebagai data pendukung. Hasil penelitian ini menunjukkan bahwa Dewan Pengawas Syariah berperan dalam implementasi kepatuhan syariah lembaga zakat sebagai pengawas dan pembina. Peran DPS secara empiris, selain memberikan opini syariah, fatwa syariah. Sudah menjadi peran DPS untuk memberikan edukasi terkait zakat kepada para pelaku di lembaga zakat. DPS memiliki peran vital dan positif dalam kualitas pelaporan keuangan karena di sisi lain, muzaki membutuhkan transparansi dan akuntabilitas penggunaan dana zakat. Dewan Pengawas Syariah (DPS) harus memastikan dana zakat dihitung dengan benar, dilaporkan secara transparan, dan didistribusikan secara merata kepada penerima zakat.